Treatment Efficacy Cognitive-Communicative disorders resulting from traumatic brain injury in adults - Coelho, Carl A; Deruyter, Frank; Stein, Margo (Journal of Speech Language and Hearing Research, 1996)
Traumatic brain injuries (TBI) may result in a broad array of cognitive-communicative impairments. Cognitive-communicative impairments are the result of deficits in linguistic and nonlinguistic cognitive functions. The speech-language pathologist functions as a member of the multidisciplinary team of professionals that collaboratively assess and treat individuals with TBI. The role of the speech-language pathologist includes assessment of all aspects of communication, as well as the communicative implications of cognitive deficits, and swallowing; treatment planning and programming, as determined by the individual's stage of recovery; client and family training/counseling; and interdisciplinary consultation. The effectiveness of speech and language intervention for specific cognitive deficits (e.g., attention, memory, executive functions) as well as general issues of social-skills training and early intervention are illustrated by scientific and clinical evidence from group-treatment and single-subject studies as well as case studies.
46 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/044-522-997-910-510 tex.type: [object Object]
Keywords: *Brain Injuries/co [Complications]; *Cognition Disorders/et [Etiology]; *Cognition Disorders/th [Therapy]; *Communication Disorders/et [Etiology]; *Communication Disorders/th [Therapy]; Activities of Daily Living; Brain Injuries; Brain Injuries/pp [Physiopathology]; Cognition Disorders; Cognitive rehabilitation; Communication Disorders; Communication disorders; Humans; Intervention studies; Speech Therapy; Traumatic brain injury; Treatment Outcome; Treatment outcome; adult; article; attention; brain injury; cognitive defect; communication disorder; consultation; counseling; daily life activity; dept.cmd; female; human; linguistics; major clinical study; male; memory; quality of life; social adaptation; speech therapy; treatment outcome; treatment planning; ⛔ No DOI found

An Investigation of a Method of Simplified Scoring for the Kaufman Hand Movements Test as a Measure of Limb Apraxia: - Neiman, Michael R.; Duffy, Robert J.; Belanger, Steven A.; Coelho, Carl A. (Perceptual and Motor Skills, 1996)
A simplified, 3-category method for scoring the Kaufman Hand Movements test was devised to replace a previously used, more complex 21-category scoring method. The concurrent validity and diagnostic sensitivity of the rescored test as a measure of limb apraxia were investigated in a reanalysis of the test protocols of 23 aphasic adults. Using the Limb Apraxia Test as the criterion measure, a Pearson r of .71 and predictive validity of 100% were obtained. These results encourage further investigation of the Kaufman Hand Movements lest as an efficient measure of limb apraxia.
0 citations (Crossref) [2023-10-31]
Keywords: Adult; Aged; Aphasia; Apraxias; Dominance; Cerebral; Female; Humans; Imitative Behavior; Male; Middle Aged; Motor Skills; Neuropsychological Tests; Observer Variation; Orientation; Psychometrics; adult; aged; aphasia; apraxia; article; dept.cmd; female; hemispheric dominance; human; imitation; male; middle aged; motor performance; neuropsychological test; observer variation; orientation; psychometry; statistics